PENGARUH NILAI SAHAM, PROFITABILITAS DAN PAJAK PENGHASILAN TERHADAP PERATAAN LABA PADA PERUSAHAAN PROPERTI DAN REAL ESTATE - Suharto, Suharto; Sujana, I Ketut (E-Jurnal Akuntansi; Vol 17 No 3 (2016), 2016)
Research on smoothing earnings and the factors that influence is very important in order to avoid asymmetries of information contained in the financial statements to the media for investors and principals to assess the performance management of a company. This study aims to provide empirical evidence of the influence of shareholder value, profitability and income tax on income smoothing practices. This study uses data on properties and real estate companies listed on the Indonesia Stock Exchange 2010-2014. The samples in this study using purposive sampling method. The number of observations in this study of 135 sample. Technical analysis of the data used is the logistic regression analysis. Based on the analysis found that the value of shares and the income tax has no effect on income smoothing. While the profitability of a positive effect on income smoothing.
Keywords: Income smoothing, stock value, profitability, income tax